Rabies control in South Asia requires a One Health approach - Acharya, Krishna Prasad (One Health, 2021)
Rabies is a vaccine-preventable viral disease present in more than 150 countries around the world. Globally, almost 60,000 people die each year from rabies, of which more than 58% are in Asia and around 45% in South Asia with especially high incidence in India, Pakistan and Bangladesh. Vaccination coverage of both people and stray dogs is low in the region and in general people are not given enough protection and information about pre- and post-exposure prophylaxis. Engagement of multiple sectors and One Health collaboration including community education, awareness programmes and vaccination campaigns are critical to control and elimination of rabies.